Structure and electrocatalytic activity of flexible reduced graphene oxide/fullerene smart fiber. (February 2019) - Zhang, Huanxia; Wu, Wen; Yu, Xili; Tong, Mingqiong; Zhou, Jie; Cao, Jianda; Gao, Pu; Zhao, Jianwei; Xu, Hong; Ma, Hui
Abstract: A strategy to prepare flexible reduced graphene oxide/fullerene (RGO/C60 ) smart fiber by utilizing a wet-spinning assembly of graphene oxide (GO) and hydroxylated fullerene and followed underwent chemical reduction is presented. Zero-dimensional fullerene acts a capture introduced into reduced graphene oxide fiber and causes a significant improvement of trapping free radicals and accessible surface area to chemicals, finally entrusting the electrocatalytic activity to reduced graphene oxide fiber. We found that C60 -intervention might induce the disordered structure of RGO layers turning into an ordered one. Moreover, the 95/5-RGO/C60 fiber displayed the highest surface area of 42.03 m 2 /g and the maximum micropore volume of 46.43 × 10 −3  mL/g compared with those of pure RGO (27.22 m 2 /g and 24.75 × 10 −3  mL/g respectively) and other fibers with different mass ratio. Additionally, the rhodamine B catalyzed by the 95/5-RGO/C60 fiber produced better degradation efficiency (70% within 48 h) than pure RGO fiber (35% within 48 h). The results of electrical resistivity analysis revealed that the RGO/C60 fibers have high electrosensitivity under different thermal and mechanical conditions. This work provides fundamental insight into the effect of the RGO layers turning in hybrid fibers and sheds light on the design of next-generation sensitive and high flexible smart sensor. Graphical abstract: Image 1